Optimizing vertical-axis wind turbine designs: A comparative CFD analysis of savonius, darrieus, and savonius-darrieus configurations - Erizon, Nelvi; Refdinal, Refdinal; Jasman, Jasman; Irzal, Irzal; A, Yufrizal; Fahrezi, Muhammad Shadiq; Fernanda, Firza; Fadillah, Egi; Pepito, Ma Leona Maye B. (Teknomekanik, 2025)
This study aims to evaluate the performance of vertical-axis wind turbines (VAWTs) with three different configurations, including Savonius, Darrieus, and a Savonius-Darrieus hybrid wind turbine, using Computational Fluid Dynamics (CFD) simulations. The methodology involves 3D geometry modeling, simulation parameter setup, meshing, and post-simulation analysis using SolidWorks 2022 software. The simulation results indicate that the Savonius turbine achieves the highest power coefficient (Cp) and torque coefficient (Ct) among the three designs, with a maximum Cp value of 0.5 at a Tip-Speed Ratio (TSR) of 0.4. Conversely, the hybrid turbine demonstrates lower efficiency, although it theoretically offers potential for improving performance at low wind speeds. Pressure and flow velocity distributions reveal that the Savonius turbine maintains the most stable pressure pattern compared to the other configurations. These findings highlight the potential of the Savonius turbine as a small-scale renewable energy solution, particularly in urban areas with low wind speeds. Further research is recommended to optimize hybrid turbine designs using machine learning approaches and empirical validation through field experiments to support the achievement of Sustainable Development Goals (SDGs), particularly Goal 7, affordable and clean energy.